Risk management for cybersecurity and IT managers (Packt Publishing, 2018)
"Have you ever wondered why your organization's executives or your manager made a decision to fund or not fund your project? In this course, you will get an inside look at how cybersecurity and information technology (IT) managers determine which projects they will support with funding and which they won't based on a preliminary risk analysis. Over the past two decades, I have worked in the cybersecurity and information technology realm, fighting for my projects to become funded. Early in my career, I didn't understand why certain projects would be funded and executed, while others wouldn't. What I learned, it all came down to risk management by our executives and managers. You will learn the terms used by executives and managers in discussing risk management, and how to apply the concepts of risk management to your networks, systems, and projects. This course is not an operational or tactical course that focuses on how you will secure your networks, but instead focuses on the mindset of managers and teaches you how to think like they do. Once you master these concepts, it is much easier to build your business case for your projects and justify your budgetary needs. This course also includes two case studies of what happens when risk management fails, as demonstrated by the Amazon Web Services outage and Equifax data breach that both occurred in 2017"--Resource description page